Paradiplozoon homoion Bychowsky & Nagibina, 1959 versus P. gracile Reichenbach-Klinke, 1961 (Monogenea): two species or phenotypic plasticity? - Matejusová, I; Koubková, B; Gelnar, M; Cunningham, C O (Systematic parasitology, 2002)
Specimens of the Paradiplozoon homoion-complex were collected from ten species of cyprinid fish in the Czech Republic. A combined molecular and morphometric approach was performed to distinguish Paradiplozoon homoion and P. gracile. The second internal transcribed spacer (ITS2) of the ribosomal RNA genes was amplified and sequences were analysed. No variability in the analysed sequences was detected. Measurements of clamps and the central hooks obtained from specimens from different host species were compared. Great variability was found in the length and width of the third pair of clamps. No significant differences were detected in the measurements of the central hook sickle. A positive relationship was found between host size and each of the following measurements of the third pair clamps: length and width of the whole clamp; and length of the median plate of the third pair of clamps. The length of the median plate of the attachment clamps may be a useful character for species identification of diplozoids. Further molecular and morphometric studies are required to resolve this taxonomic problem and, henceforth, we suggest considering P. gracile as a species inquirenda.
Keywords: DNA, Ribosomal Spacer; Sequence Analysis, DNA; Gills; Česká republika; žábry; genetická variace; RNA helmintů; Trematode Infections; fenotyp; Cyprinidae; Czech Republic; Genetic Variation; Phenotype; zvířata; nemoci ryb; RNA, Helminth; Species Specificity; Trematoda; sekvenční analýza DNA; Fish Diseases; druhová specificita; RNA ribozomální; RNA, Ribosomal; mezerníky ribozomální DNA; infekce červy třídy Trematoda; Animals